Modeling and Optimization of Socio-Economic Aspects for the Development of Tourism - KULAKHMETOVA, Gulbaram A.; SHCHERBAKOVA, Nadiia A.; TSYPKO, Victoria V. (Journal of Environmental Management and Tourism, 2019)
The paper deals with the variants of providing digital nomadism with tourist services and service under conditions of global informatization. In order to increase the mobility of this category of tourists, the authors offered a model of information support in accordance with the strategy of global geoinformation supporting of travel infrastructure. The navigation system of information depository is focused on the localization of life support system points with optimal combination of infrastructure objects. For filling the information depository of tourist destination determination and annotation of most significant objects and access points to global tourist system of informatization have been carried out.  When choosing the above-mentioned objects, the authors proceeded from the following founding principles: accessibility of objects to Internet system sources; consumer preferences; security. To ensure quality of tourist services and service the analysis of the state of global tourist information system infrastructure is carried out in the paper. Following the findings, proposals for the implementation of information depository model are developed. The markers of system orientation in space providing the link of object location with geoinformation field are included in the depositary information field. In general, the offered model, according to authors, will contribute to comfortable and safe movement of digital nomads on tourist route.